The Penerapan SIA Persediaan Suku Cadang Pada PT Perkebunan Nusantara 1 Region 7 - Shahib Hibatullah Malik; Siti Khairani (MDP Student Conference, 2026)
This research is a qualitative research that aims to find out how the spare parts inventory accounting information system at PT. Perkebunan Nusantara 1 Regional 7 Sungai Niru Factory. Data collection techniques through observation and interviews. The results of the study indicate that at the beginning of the process of implementing the use of accounting information systems there are challenges in implementing accounting information systems using SAP applications where the company still uses manual methods, namely Excel, to record spare parts inventory, challenges need to be developed in using SAP applications because this will help the company fully in working efficiently.